2013
DOI: 10.2111/rem-d-11-00130.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Impacts of Roads: Application of a Standard Assessment Protocol

Abstract: Adaptive management of road networks depends on timely data that accurately reflect the impacts those systems are having on ecosystem processes and associated services. In the absence of reliable data, land managers are left with little more than observations and perceptions to support management decisions of road-associated disturbances. Roads can negatively impact the soil, hydrologic, plant, and animal processes on which virtually all ecosystem services depend. The Interpreting Indicators of Rangeland Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Perhaps somewhat surprisingly, none of the identified ES hotspots were located in currently protected areas; possibly due to inaccessibility. The importance of ES proximity to roads was highlighted by Chan et al (2006) and Fagerholm et al (2012), suggesting there may be trade-offs in trying to achieve a high level of both biodiversity and ES in the same area, since roads are also known to negatively impact biodiversity along with many of the biological processes and functions that ES depend upon (Duniway and Herrick, 2013). A recent review by Mitchell et al (2013) revealed that there is little known regarding how connectivity and road access affect ES delivery (especially for cultural ES and provisioning ES), and that links between cultural ES and connectivity have never been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps somewhat surprisingly, none of the identified ES hotspots were located in currently protected areas; possibly due to inaccessibility. The importance of ES proximity to roads was highlighted by Chan et al (2006) and Fagerholm et al (2012), suggesting there may be trade-offs in trying to achieve a high level of both biodiversity and ES in the same area, since roads are also known to negatively impact biodiversity along with many of the biological processes and functions that ES depend upon (Duniway and Herrick, 2013). A recent review by Mitchell et al (2013) revealed that there is little known regarding how connectivity and road access affect ES delivery (especially for cultural ES and provisioning ES), and that links between cultural ES and connectivity have never been tested.…”
Section: Discussionmentioning
confidence: 99%
“…Soil and vegetation attributes were sampled at 120 plots as part of a broader study to evaluate the sensitivity of a standard rangeland assessment protocol to road impacts (Duniway and Herrick 2013). The plots were stratified across five types of ecological site with similar potential vegetation composition and vegetation production ( Table 1; Appendix: Table A1).…”
Section: Field Data Collectionmentioning
confidence: 99%
“…Further, our work suggests that most participants who perceived an increase in ecosystem services were in favour of increased road development to access ecosystem services. Many previous studies suggest road access is important for many provisioning ecosystem services (Chan et al 2006;Wang et al 2010;Fagerholm et al 2012;Cimon-Morin et al 2013), yet roads are known to negatively impact regulating and supporting ecosystem services through degradation to plant, animal, soil and hydrologic processes (Benítez-López et al 2010;Duniway and Herrick 2013). Different stakeholder groups may have different influence in management decisions despite all having strong interest, value or use of ecosystem services.…”
Section: Discussionmentioning
confidence: 99%